Changes in Attenuated Total Reflection Fourier Transform Infrared Spectra as Blood Dries Out1. Issue 3 (16th December 2016) - Zhang, Yinming; Wang, Qi; Li, Bing; Wang, Zhijun; Li, Chengzhi; Yao, Yao; Huang, Ping; Wang, Zhenyuan
Abstract: The time since deposition (TSD) of a bloodstain is a valuable piece of evidence for forensic scientists to determine the time at which a crime took place. The objective of this study was to determine whether attenuated total reflection (ATR) Fourier transform infrared (FTIR) spectroscopy could be used to estimate the TSD of a bloodstain in a relatively early period (from 0 min to the time required for the bloodstain to dry out). For this purpose, we used ATR‐FTIR to study the variation in absorbance at certain wavelengths as rat and human blood sample dried out. The absorbance at 3308/cm (A3308) was found to have a close correlation with the TSD during this time period, and the changes in A3308 during the drying of rat and human blood drops under the same controlled conditions showed similar results. The current study indicates that ATR‐FTIR spectroscopy has potential as a tool for estimating TSD at early time periods of blood deposition.